Pengaruh Penambahan Berbagai Jenis Bokashi Terhadap Pertumbuhan dan Hasil Tanaman Selada - F. H. Listyorini; Linda E. Lindongi (Fakultas Pertanian Universitas Papua, 2009)
This research conducted to determine the type of bokashi which gave the best growth and yield of lettuce. Complete randomized design was used in this present study with five types of bokashi as a treatment such as charcoal bokashi, ash bokashi, ashcharcoal bokashi and soil bokashi including none bokashi treatment as a comparison. The result of this experiment showed that bokashi addition increased the plant length, leaf number and shoot fresh weight comparing to none bokashi treatment. Further, even though there was no significantly different in terms of lettuce length and leaf number as comparing to soil bokashi, but charcoal bokashi, ash bokashi and ashcharcoal bokashi gave higher shoot fresh weight. Generally, among all bokashi treatments, ash bokashi showed to give the best growth and yield of lettuce with the increased percentage compare to none bokashi treatment for about 1061.8% followed by ash-charcoal bokashi, charcoal bokashi and soil bokashi with 711.8%, 522.2% and 497% in respectively.